(untitled) (International Journal of Ayurveda and Pharma Research, 2015)
Prakriti (Constitution) of a person are seven different types based on the dominancy of Doshas. The Prakriti of a person is determined by the predominance of a particular Doshas at the time of conception and also influenced by the environmental factors. Prakriti has direct influence on the academic performance of the children as the memory and intelligence is governed by dominance of Doshas in our body. For identification of Prakriti we depend upon certain criterias which are mostly based on physiological, anatomical and psychological factors. By knowing Prakriti of children we can apply useful guidelines on them which may help them to make a right judgment and attitude towards life. It will also help to form a useful frame work for future of children. With this preview present study was conducted to assess the correlation between academic performance and Prakriti childhood period. Healthy volunteers were selected randomly from the survey done and OPD of NIA, Jaipur. 140 children were selected for the study after taking informed consent. There Prakriti was assessed and digit span test was done to retest impact of Prakriti on memory of the children. The comparison between the memory counted from proformas and digit span test was done. It was found that out of seven types of Prakriti that the subjects which include Vata and Pitta dominancy have good short term memory and subjects with Vata dominancy have good short term memory.